Maternal well-being and its association to risk of developmental problems in children at school entry - Benzies Karen; Siever Jodi E; Tough Suzanne C; Leew Shirley; Johnston David W (BMC, 2010)
Abstract Background Children at highest risk of developmental problems benefit from early identification and intervention. Investigating factors affecting child development at the time of transition to school may reveal opportunities to tailor early intervention programs for the greatest effectiveness, social benefit and economic gain. The primary objective of this study was to identify child and maternal factors associated with children who screened at risk of developmental problems at school entry. Methods An existing cohort of 791 mothers who had been followed since early pregnancy was mailed a questionnaire when the children were aged four to six years. The questionnaire included a screening tool for developmental problems, an assessment of the child's social competence, health care utilization and referrals, and maternal factors, including physical health, mental health, social support, parenting morale and sense of competence, and parenting support/resources. Results Of the 491 mothers (62%) who responded, 15% had children who were screened at high risk of developmental problems. Based on a logistic regression model, independent predictors of screening at high risk for developmental problems at age 5 were male gender (OR: 2.3; 95% CI: 1.3, 4.1), maternal history of abuse at pregnancy (OR: 2.4; 95% CI: 1.3, 4.4), and poor parenting morale when the child was 3 years old (OR: 3.9; 95% CI: 2.1, 7.3). A child with all of these risk factors had a 35% predicted probability of screening at high risk of developmental problems, which was reduced to 13% if maternal factors were favourable. Conclusions Risk factors for developmental problems at school entry are related to maternal well being and history of abuse, which can be identified in the prenatal period or when children are preschool age.